Rafael Gutiérrez Girardot's Elective Affinity: Walter Benjamin (2021)
This article attempts to understand two aspects of Latin American thinking. The first is the existence of a longlasting dialogue between European and American writers. The second is the placing of the Colombian philosopher Rafael Gutiérrez Girardot within this dialogue on the basis of his interpretation of Walter Benjamin's work. The article also seeks to set a path for future research on cultural reception